[RETRACTED ARTICLE] Applying the Model of Goal-Directed Behavior to Explain Cycling Behaviors Characterised by Traveler’s Gender and Car Ownership in Chonburi Urban Areas - Intanu, Chaturong; Piriyawat, Surames (Engineering and Technology Horizons, 2021)
This article has been retracted by the editorial team of Engineering and Technology Horizons (formerly known as the Ladkrabang Engineering Journal). An editorial assessment identified data discrepancies and conflicts between this article and an article published in another journal that uses the same foundational dataset. In accordance with the journal’s ethical policies and the Committee on Publication Ethics (COPE) Guidelines, the article has been formally retracted. Please note that this administrative action is based strictly on the objective presence of conflicting data to maintain the integrity of the academic record and does not constitute a conclusion regarding the intent or liability of any party involved.